2014
DOI: 10.9790/2402-08940110
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Statistical Evaluation of Heavy Metals in Respirable Dust in Jos Metropolitan Area, Nigeria

Abstract: The concentration of heavy metals in respiration dust (˂10µg) within Jos Metropolis was monitored in seven sites made up of two industrial and high traffic areas each, with residential site as control were studied for nine consecutive months (October, 2013 to June, 2014). The concentrations of the heavy metals were studied in terms dust mass, time dependence and safety. The mass of respirable dust ranged from 0.079-0.288g, while the mean concentration ranged from 49-208ug/m 3. Flame Atomic Absorption Spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Concentrations of all metals exceeded limits set by the WHO, with high levels of cadmium and lead posing potential cancer risks, especially for children. Mafuyai et al (2014) also Investigated heavy metals (Pb, Mn, Cd, Zn, Cr, Ni, Cu, and Fe) in respirable dust from seven locations in Jos metropolis, Plateau state. Concentrations of cadmium, nickel, and manganese greatly exceeded WHO-recommended limits, indicating vehicular traffic and waste incineration as sources.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
“…Concentrations of all metals exceeded limits set by the WHO, with high levels of cadmium and lead posing potential cancer risks, especially for children. Mafuyai et al (2014) also Investigated heavy metals (Pb, Mn, Cd, Zn, Cr, Ni, Cu, and Fe) in respirable dust from seven locations in Jos metropolis, Plateau state. Concentrations of cadmium, nickel, and manganese greatly exceeded WHO-recommended limits, indicating vehicular traffic and waste incineration as sources.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
“…African farmers use farmyard manure and wastewater irrigation due to the scarcity and enormous expense of inorganic fertilizers; however, these methods may contain metals that enter the food chain and harm the soil [25]. Roadside soil contamination from automotive emissions is also pervasive in Africa due to a lack of laws or conformity with legislation [26]. Even though some African nations have pollution reduction guidelines, it is not particularly helpful if the rules and laws are not upheld.…”
Section: Cases Of Environmental Pollution In Developed and Developing...mentioning
confidence: 99%
“…Both acute and chronic exposures to carbon monoxide are associated with increased risk for adverse cardiopulmonary events, including death. However, studies have not demonstrated a clear dose-dependent health risk response to increasing amounts of these pollutants except at high concentrations [13,14].…”
Section: Introductionmentioning
confidence: 99%